Eicosanoids Derived From Arachidonic Acid and Their Family Prostaglandins and Cyclooxygenase in Psychiatric Disorders - Yui, Kunio; Imataka, George; Nakamura, Hiroyuki; Ohara, Naoki; Naito, Yukiko (Current Neuropharmacology, 2015)
Arachidonic acid (AA)-derived lipid mediators are called eicosanoids. Eicosanoids have emerged as key regulators of a wide variety of physiological responses and pathological processes, and control important cellular processes. AA can be converted into biologically active compounds by metabolism by cyclooxygenases (COX). Beneficial effect of COX-2 inhibitor celecoxib add-on therapy has been reported in early stage of schizophrenia. Moreover, add-on treatment of celecoxib attenuated refractory depression and bipolar depression. Further, the COX/prostaglandin E pathway play an important role in synaptic plasticity and may be included in pathophysiology in autism spectrum disorders (ASD). In this regard, plasma transferrin, which is an iron mediator related to eicosanoid signaling, may be related to social impairment of ASD. COX-2 is typically induced by inflammatory stimuli in the majority of tissues, and the only isoform responsible for propagating the inflammatory response. Thus, COX-2 inhibitors considered as the best target for Alzheimer’s disease.
Keywords: cyclooxygenases-1 inhibitors